Patience Reflected In Okky Madasari's Bound (2013) Novel: A Psychoanalytic Approach. - Amin Nugroho, Akbar; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is patience. The objective of this study is to analyze Okky Madasari's Bound novel based on the structural elements and analyze this novel based on the Psychoanalytic Approach. The writer employs descriptive qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then, the secondary data sources are the books about psychoanalysis, references from internet about Bound novel, references about patience theory, and other sources, which are have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the analysis, the writer get some conclusions. The study shows that the problem faced by the major character is his own patience and psychology condition. It is proved by his struggle and patience in daily activity by being two role in one life story, that is being Sasana and Sasa.